(untitled) (Portuguese Journal of Family Medicine and General Practice, 2024)
Introduction: Adherence to therapy is a frequent challenge in family medicine. This case report aims to raise awareness of the utility of family assessment instruments as an effective ally in addressing the challenge of managing therapeutic adherence. Case description: Woman, 77 years old, married, diagnosed with anxiety disorder, arterial hypertension, and dyslipidemia. She presented a record of high blood pressure values in the medical appointments of the last four years but remained resistant to any therapeutic change suggested by her family doctor. In this context, the patient was called to carry out a family evaluation, to understand her fears, beliefs, and expectations. A history of conflict with her husband was found, with a past of adultery that led to a severe depressive disorder, requiring polymedication. Faced with this memory, any attempt at a therapeutic change led to great anxiety in the patient. A review of her current therapy was established as a plan, to optimize it without changing the number of daily pills. In the subsequent medical appointments, there was complete adherence to the instituted therapy. Comment: This case report highlights two very important aspects of the practice of family medicine. It reinforces the family assessment instruments’ importance in understanding the context of our patients and it also shows the need for the adaption of the family doctor when faced with cases in which the best available treatment is not the most suitable for the patient, who carries with him a set of beliefs and expectations. Thus, attention is drawn to the need for the so-called patient-tailored interventions – we should try to adjust our expectations to our patients’ reality and provide a therapy that is as individualized as possible.